Knockdown of phospholipase C-beta 1 in the medial prefrontal cortex of male mice impairs working memory among multiple schizophrenia endophenotypes - Kim, Seong-Wook; Seo, Misun; Kim, Duk-Soo; Kang, Moonkyung; Kim, Yeon-Soo; Koh, Hae-Young; Shin, Hee-Sup (CMA-CANADIAN MEDICAL ASSOC, 2015)
Background: Decreased expression of phospholipase C-beta 1 (PLC-beta 1) has been observed in the brains of patients with schizophrenia, but, to our knowledge, no studies have shown a possible association between this altered PLC-beta 1 expression and the pathogenesis of schizophrenia. Although PLC-beta 1-null (PLC-beta 1(-/-)) mice exhibit multiple endophenotypes of schizophrenia, it remains unclear how regional decreases in PLC-beta 1 expression in the brain contribute to specific behavioural defects. Methods: We selectively knocked down PLC-beta 1 in the medial prefrontal cortex (mPFC) using a small hairpin RNA strategy in mice. Results: Silencing PLC-beta 1 in the mPFC resulted in working memory deficits, as assayed using the delayed non-match-to-sample T-maze task. Notably, however, other schizophrenia-related behaviours observed in PLC-beta 1(-/-) mice, including phenotypes related to locomotor activity, sociability and sensorimotor gating, were normal in PLC-beta 1 knockdown mice. Limitations: Phenotypes of PLC-beta 1 knockdown mice, such as locomotion, anxiety and sensorimotor gating, have already been published in our previous studies. Further, the neural mechanisms underlying the working memory deficit in mice may be different from those in human schizophrenia. Conclusion: These results indicate that PLC-beta 1 signalling in the mPFC is required for working memory. Importantly, these results support the notion that the decrease in PLC-beta 1 expression in the brains of patients with schizophrenia is a pathogenically relevant molecular marker of the disorder.
Keywords: ACETYLCHOLINE-RECEPTOR SUBTYPES; KNOCKOUT MICE; FUNCTIONAL CONNECTIVITY; ANTERIOR CINGULATE; THETA OSCILLATIONS; INDUCED DEFICITS; AGONIST; RAT; ACTIVATION; SYNCHRONY